Villiam Grønbæk: Psykologiske tanker og teorier hos Grundtvig - Lindhardt, P. G. (Grundtvig-Studier, 1952)
Villiam Grønbæk: Psykologiske tanker og teorier hos Grundtvig. (Grundtvig s Psychological Ideas and Theories.) Skrifter udg. Af Grundtvig-Selskabet IV, København 1951. (Publications of the Grundtvig Society IV, Copenhagen 1951). Reviewed by P. G. Lindhardt. This book does not deal with Grundtvig’s own psychological development, but attempts to present Grundtvigs ideas about psychology, and in so doing also prepares the way for a complete presentation of Grundtvig’s anthropological theories. The author, who is well known as an expert on the psychology of religion, uses his thorough knowledge of modern psychology to describe Grundtvig’s theories about “ foreboding” (intuition) and “ longing” (favourite words of the Romantic Movement) and “ experience” and “ self-consciousness” (the leading philosophical concepts of the eighteenth century). Grundtvig in his youth acquired a thorough knowledge of contemporary psychological theories, as is made evident by a series of unpublished notes which Dr. Grønbæk reproduces (with occasional misreadings). But Grundtvig never became the disciple of any particular psychologist; he formed his own theories independently, e. g., his famous tripartite psychological division of man’s mental life into imagination, feeling and understanding. In his treatment of these ideas, which were central in Grundtvig’s work as a writer, the book is of great general interest to all students of Grundtvig. Of great value, too, is the presentation of Grundtvig’s view of man as consisting of body, soul and spirit. For Grundtvig the body is not something base and of no consequence, as it is for so many idealist philosophers; man in his whole nature is created by God and in God’s image (Grundtvig can even conceive of his tripartite psychological division mentioned above as mirroring the Trinity), and his contact with the Divine is maintained, first and last, through the word, which is both physical (spoken by the mouth and apprehended through the ear) and spiritual. The book also discusses Grundtvig’s ideas concerning the will and the conscience, faith and the heart, and the different periods of human life. The fundamental religious experience which Grundtvig describes in the words: “When the heart warmly / Takes hold on the word, / Then we embrace our Saviour” is discussed in the light of the theories of the modern experimental psychologist, W. Gruehn, and his conception of human nature is compared with Stern’s psychology of the individual. Thus the book not only directs its attention to Grundtvig’s own period, but it is also a contribution to modern psychological studies. The author’s comments on the fundamental questions of the psychology of influence are of the greatest interest. The reviewer also considers that the book not only represents a conquest of new territory in Grundtvig research, but also throws light on many obscure points in the more recent history of Grundtvigianism, and should thus be of great help to students of this most singular sociological and psychological phenomenon in the history of our Church.